Composite Lithium Anodes: Sowing Silver Seeds within Patterned Ditches for Dendrite‐Free Lithium Metal Batteries (Adv. Sci. 14/2021) - Wang, Hua (Adv Sci (Weinh), 2021)
In article number 2100684, Zhen Li, Yunhui Huang, and co‐workers develop a highly stable lithium anode with silver nanowires sowed in the patterned ditches by a simple calendaring process. The modified lithium anode works like growing crops. In the image, by sowing the seeds (silver nanowires) in the ditches, people can harvest rich fruits (green energy) after careful cultivation. [Image: see text]